Factors Associated with Oral Health-Related Quality of Life in Preschoolers of Concepción, Chile: A Cross-Sectional Study - Ricardo Cartes-Velásquez; Yanara Nauduam-Elgueta; Gabriela Sandoval-Bustos; Valeria Campos; Roberto Antonio León-Manco; Luis Luengo (Association of Support to Oral Health Research (APESB), 2022)
Objective: To identify the factors associated with Oral Health-Related Quality of Life (OHRQoL) in preschool children of Concepción, Chile. Material and Methods: A cross-sectional study was conducted in a sample of enrolled preschoolers who attend public schools in Concepción, Chile. To measure OHRQoL, the chilean version of the Early Childhood Oral Health Impact Scale (ECOHIS) was used; sociodemographic variables of the children and their parents were also recorded, as well as variables regarding the last visit to the dentist. To determine differences in the ECOHIS score for categorical variables, ANOVA and t-test were used, while Pearson's r was used to correlate ECOHIS with quantitative variables (p<0.05). Results: A total of 175 children were surveyed, with a distribution of 89 boys and 86 girls aged 56-to-79 months. The total score of the ECOHIS had a mean of 4.48 ±5.96, with a score between 0-38. Statistically significant associations were with parent's educational attainment (r=-0.159), dmft (r=0.380), OHI-S debris (r=0.174) and reason for the last visit to the dentist, the highest average in the ECOHIS scores was registered in the urgency reason. Conclusion: Oral health status, dental service utilization and educational level are associated with the OHRQoL of preschoolers of Concepción.